CREATION OF A MODERN MODEL OF REDUCTION OF CARBON TOXIC GASES IN INDUSTRY - Akmalov Sayfiddin Akmal o’gli (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: In this scientific article, with the development of industry, the demand for reducing carbon dioxide toxic gases on the planet is increasing. In addition, various scientific studies have been conducted based on the increasing demand for determining the composition of toxic gases in the air and building a modern model of production sources that lead to their increase, thereby building new models in terms of environmentally harmful gases. By combining a two-way fixed effect model, a mediated effect model, and a panel threshold model, this research endeavors to explore the effect that the expansion of the digital economy has on the level of carbon emission intensity that is produced by industry. The research yielded the following primary conclusions. The digital economy effectively reduces the industrial carbon intensity via three distinct mechanisms: enhancements to the technological and innovative capacities of industries, improvements in energy efficiency, and enhancements to the country’s overall industrial structure. This research offers a theoretical backing for advancements in the digital economy; the achievement of energy-saving and carbon-reducing sustainable development objectives; and the establishment of green, ecologically friendly, and recycling development strategies.